2022
DOI: 10.2169/internalmedicine.8113-21
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Ischemic Versus Hemorrhagic Stroke in Patients Receiving Oral Anticoagulants: Results of the PASTA Study

Abstract: Objective Limited data exist regarding the comparative detailed clinical characteristics of patients with ischemic stroke (IS)/transient ischemic attack (TIA) and intracerebral hemorrhage (ICH) receiving oral anticoagulants (OACs). Methods The prospective analysis of stroke patients taking oral anticoagulants (PASTA) registry, a multicenter registry of 1,043 stroke patients receiving OACs (vitamin K antagonists [VKAs] or non-vitamin K oral antagonists [NOACs]) across 25 medical institutions throughout Japan, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Because real-world Japanese data indicated that the use of OACs was increasing and DOACs were rapidly replacing warfarin in patients with non-valvular atrial fibrillation 7 , these situations might result in an increment in the rate of prior DOAC users in Japanese SICH. Indeed, a prospective Japanese multi-stroke center cohort (the PASTA registry) that enrolled acute stroke patients receiving prior OAC from April 2016 to September 2019 showed a similar rate of prior OAC use in SICH (DOACs 73% vs warfarin 27%) 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Because real-world Japanese data indicated that the use of OACs was increasing and DOACs were rapidly replacing warfarin in patients with non-valvular atrial fibrillation 7 , these situations might result in an increment in the rate of prior DOAC users in Japanese SICH. Indeed, a prospective Japanese multi-stroke center cohort (the PASTA registry) that enrolled acute stroke patients receiving prior OAC from April 2016 to September 2019 showed a similar rate of prior OAC use in SICH (DOACs 73% vs warfarin 27%) 33 .…”
Section: Discussionmentioning
confidence: 99%
“…A study by Lin et al showed that patients with recurrent AIS despite DOAC therapy were more likely to suffer from a malignancy [ 34 ]. A study by Suda et al showed that high levels of B-type natriuretic peptide, suggestive of congestive heart failure, were independently associated with AIS or TIA despite the use of oral anticoagulants (DOAC or VKA) [ 35 ].…”
Section: Discussionmentioning
confidence: 99%